La inserción laboral de personas con discapacidad en el campo empresarial. - Analuisa Zumba, Tatiana Paola; Roman Escobedo, Viviana Amparo (My University, 2020)
In Ecuador, with the validity of the 2008 Constitution, new labor policies are created to promote the hiring of people with disabilities in the business field. These policies try to guarantee the inclusion and respect for the rights of these historically discriminated population. It is at this point, where the criteria of many entrepreneurs becomes antag-onistic since they do not know whether this type of compulsory contracting becomes an unnecessary expense in labor, or whether it could be a benefit for the business sector they represent. Therefore, this qualitative research aims to elucidate the opin-ions of representatives of the business sector in El Oro province- Ecuador regarding the contracting of individuals with disabilities. The results show that such contracting practices help to strengthen the corporate image, increase internal competitiveness and more humane working environment as well as getting tax benefits. It is concluded that the employment of persons with disabilities constitutes a benefit for the business sector.
En el Ecuador con la vigencia de la Constitución del 2008, surgen nuevas políticas laborales encaminadas a promover la contratación de personas con discapacidad en el campo empresarial, políticas que intentan garantizar la inclusión y el respeto de los derechos de estas personas históricamente discriminadas; es en este punto, donde el criterio de muchos empresarios es antagónico, incierto al no saber si este tipo de contratación de carácter obligatorio se convierte en un gasto innecesario en mano de obra, o se podría constituir en un beneficio para el sector empresarial que representan. Aspecto que la presente investigación tiene como objetivo dilucidar, mediante la revisión bibliográfica e investigación cualitativa aplicada a representantes del sector empresarial de la Provincia de El Oro – Ecuador. A través de los resultados obtenidos se logran identificar beneficios para el sector empresarial como: fortalecimiento de imagen corporativa, incremento de competitividad interna, clima laboral más humano y otros beneficios tributarios; se llega a la conclusión de que la contratación laboral de las personas con discapacidad constituyen un beneficio para el sector empresarial.
Keywords: INSERCIÓN LABORAL; DISCAPACIDAD; SECTOR EMPRESARIAL; BENEFICIOS